2022
DOI: 10.1186/s12884-022-04635-w
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the gut microbiota in pregnant women with fetal growth restriction

Abstract: Background Fetal growth restriction (FGR) in utero leads to failure of fetus to reach the genetically normal growth potential. Currently available means of treating FGR are limited. And it remains unknown how pregnant women who give birth to FGR fetus differ in gut microbiota composition from normal pregnant women. Methods In this case-control study, fecal samples were obtained from maternal rectum in the operation room by an obstetrician under str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
3
12
0
Order By: Relevance
“…It also turned out that Oscillospira and Coprococcus are involved in the synthesis of butyrate, which is a source of energy for intestinal epithelial cells. Consistent with our results, a study by Tu et al, evaluating the feces of infants with FGR, showed significant differences in the growth of Bacteroides, Faecalibacterium and Lachnospira in patients with growth restriction [37].…”
Section: Discussionsupporting
confidence: 93%
“…It also turned out that Oscillospira and Coprococcus are involved in the synthesis of butyrate, which is a source of energy for intestinal epithelial cells. Consistent with our results, a study by Tu et al, evaluating the feces of infants with FGR, showed significant differences in the growth of Bacteroides, Faecalibacterium and Lachnospira in patients with growth restriction [37].…”
Section: Discussionsupporting
confidence: 93%
“…Patescibacteria and Myxococcota only exist in individual samples in the pregnancy group and postpartum group, respectively. We found that the relative abundance of the phylum Firmicutes was significantly higher in the pre-pregnancy and pregnancy groups than that of the postpartum group (p < 0.05), while that of Proteobacteria was enriched, which was in keeping with the results of previous studies in pregnant women [19]. Bacteroidota, a type of Gram-negative bacteria, is the main contributor to lipopolysaccharides biosynthesis.…”
Section: Changes In Community Structure and Compositionsupporting
confidence: 90%
“…Basic information such as age, body weight, gestational age, body mass index (BMI), and fasting blood glucose of the pregnant women were recorded ( Table 1 ). The inclusion and exclusion criteria for all pregnant women are as follows [ 20 ]. Inclusion criteria: (1) FGR must meet the diagnostic criteria of the “2020 Expert Consensus on FGR,” (2) singleton pregnancy, (3) age between 22 and 35, and (4) healthy pregnant women without complications such as gestational hypertension and gestational diabetes.…”
Section: Methodsmentioning
confidence: 99%